Humanized mouse models of KRAS-mutated colorectal and pancreatic cancers with HLA-class-I match for pre-clinical evaluation of cancer immunotherapies - Maria E. Davola; Olga Cormier; Madeleine Lepard; Jamie McNicol; Susan Collins; Joanne A. Hammill; Christopher Silvestri; Jonathan L. Bramson; Amy Gillgrass; Karen L. Mossman (OncoImmunology)
Cancer immunotherapy promises to treat challenging cancers including KRAS-mutated colorectal cancer (CRC) and pancreatic ductal adenocarcinoma (PDAC). However, pre-clinical animal models that better mimic patient tumor and immune system interactions are required. While humanized mice are promising vehicles for pre-clinical immunotherapy testing, currently used cancer models retain limitations, such as lack of a human thymus for human leukocyte antigen (HLA)-based education of human T cells. As cytotoxic T lymphocyte (CTL) activity underlies many immunotherapies, we developed more clinically relevant KRAS-mutated CRC and PDAC humanized cancer models using transgenic NRG-A2 mice expressing HLA-A2.1 to enable HLA-class-I match between mouse tissues (including the thymus), the humanized immune system and human tumors. Using these novel humanized cancer models and a CTL-mediated combination (immuno)therapy with clinical potential, we were able to recapitulate the complexity and therapy-induced changes reported in patient biopsies, demonstrating the use of these HLA-matched models for pre-clinical validation of novel immunotherapies.